The Gang's All Queer : The Lives of Gay Gang Members - Panfil, Vanessa R. (Book collections on Project MUSE., 2017)
Many people believe that gangs are made up of violent thugs who are in and out of jail, and who are hyper-masculine and heterosexual. Vanessa Panfil introduces us to a different world. Meet gay gang members - sometimes referred to in popular culture as "homo thugs"--Whose gay identity complicates criminology's portrayal and representation of gangs, gang members, and gang life. In vivid detail, Panfil provides an in-depth understanding of how gay gang members construct and negotiate both masculine and gay identities through crime and gang membership. She draws from interviews with over 50 gay gang- and crime-involved young men in Columbus, Ohio, the majority of whom are men of color in their late teens and early twenties, as well as on-the-ground ethnographic fieldwork with men who are in gay, hybrid, and straight gangs. Panfil provides an eye-opening portrait of how even members of straight gangs are connected to a same-sex oriented underground world. Most of these young men still present a traditionally masculine persona and voice deeply-held affection for their fellow gang members. They also fight with their enemies, many of whom are in rival gay gangs. Most come from impoverished, 'rough' neighborhoods, and seek to defy negative stereotypes of gay and Black men as deadbeats, though sometimes through illegal activity. Some are still closeted to their fellow gang members and families, yet others fight to defend members of the gay community, even those who they deem to be "fags," despite distaste for these flamboyant members of the community.